2014
DOI: 10.1080/15398285.2014.902268
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Online Health Information Seeking: A Five Survey Meta-Analysis

Abstract: Males have traditionally been more active Internet users than females; however, research indicates females are more likely to seek health information online. This meta-analysis explores the disparity, the role of age and relationship status, and strategies to improve communication. Results indicate differences are less marked than singular studies suggest. Further, males and females are more likely to use the Internet than other resources to find health information; next, they most often seek information from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 26 publications
(20 reference statements)
7
47
0
Order By: Relevance
“…Information can be easily obtained using smartphones and other electronic devices. This is in line with the trend in other countries of using the Internet to acquire health information . The recent advent of new digital media has facilitated more information gathering than was previously possible .…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Information can be easily obtained using smartphones and other electronic devices. This is in line with the trend in other countries of using the Internet to acquire health information . The recent advent of new digital media has facilitated more information gathering than was previously possible .…”
Section: Introductionsupporting
confidence: 81%
“…countries of using the Internet to acquire health information. 5 The recent advent of new digital media has facilitated more information gathering than was previously possible. 6 This change is the result of scientific and technological developments.…”
mentioning
confidence: 99%
“…Existing research suggests that there are a number of factors that come into play in source selection, including source‐related (e.g., quality, accessibility, trustworthiness) and user‐related factors (e.g., age, gender, health status). Among user‐related factors, gender has been widely identified as an influencer of health information behavior (e.g., Hallyburton & Evans, ; Powell et al., ; Stern, Cotten, & Drentea, ). Others have suggested that differences arise from gendered roles and contexts (Lorence, Park, & Fox, ; Powell et al., ; Stern et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Internet is the first resource for health information for both men and women, however men have a higher tendency toward personal interactions to find additional information (Hallyburton and Evarts, 2014). Introducing personalisation is seen as a foundation for gender equalisation in online health seeking (Hallyburton and Evarts, 2014).…”
Section: Discussionmentioning
confidence: 99%